Tingkat Depresi, Cemas, dan Stres pada Pasien Kanker yang Menjalani Kemoterapi - Johanes A. Mastan; Linda W. A. Rotty; Harlinda Haroen; Cecilia Hendratta; Pearla Lasut (Medical Scope Journal, 2024)
Abstract: Chemotherapy in cancer patients has psychological impacts which are depression, anxiety and stress. This study aimed to evaluate the levels of depression, anxiety and stress in cancer patients undergoing chemotherapy. This was a descriptive study with a cross-sectional design. Samples were obtained by using non-probability sampling with purposive sampling technique. Subjects were cancer patients undergoing chemotherapy at Prof. Dr. R. D. Kandou Hospital aged over 18 years old, not pregnant, and not having an infectious disease. Assessment of levels of depression, anxiety and stress using DASS-42. The results obtained 62 patients undergoing chemotherapy; 47 were women (75.8%). The median and interquartile age range was 52 (14.75) years and body mass index (BMI) was 22 (5.17), 42 patients having an income <3.5 million rupiahs (67%), 36 patients with duration of illness >1 year (58%) and the majority of patients (79%) were in marital status. Among subjects, 23% experienced depression, 40% experienced generalized anxiety disorder, and 21% experienced stress. In conclusion, patients undergoing chemotherapy can experience depression, anxiety and stress disorders. Keywords: depression; anxiety; stress; chemotherapy; cancer patients   Abstrak: Kemoterapi pada pasien kanker memiliki dampak psikis yaitu depresi, cemas, dan stres. Penelitian ini bertujuan mengetahui tingkat depresi, cemas, dan stres pada pasien kanker yang menjalani kemoterapi. Jenis penelitian ialah deskriptif dengan desain potong lintang. Sampel diperoleh menggunakan non-probability sampling dengan teknik purposive sampling. Subjek penelitian ialah pasien kanker yang menjalani kemoterapi di RSUP Prof. Dr. R. D. Kandou dengan usia di atas 18  tahun, tidak hamil, dan tidak sedang dalam pengobatan penyakit infeksi. Penilaian tingkat depresi, cemas, dan stres menggunakan DASS-42. Hasil penelitian mendapatkan 62 pasien yang menjalani kemoterapi; 47 pasien ialah perempuan (75,8%). Median dan interquartil range usia ialah 52 (14,75) tahun dan  IMT 22(5,17), dengan 42 pasien mempunyai pendapatan <3,5 juta rupiah  (67%),  36 pasien dengan lama sakit  >1 tahun (58%) dan sebagian besar pasien (79%) dalam status kawin. Sebanyak 23% pasien mengalami depresi, 40% gangguan cemas menyeluruh, dan 21% mengalami stres. Simpulan penelitian ini ialah pasien yang menjalani kemoterapi dapat mengalami gangguan depresi, cemas dan stres. Kata kunci: depresi; cemas; stres; kemoterapi; pasien kanker